The imagined place in the Andalusian war poem in the Almohad and Bani Al-Ahmar eras - ايمان جليل طعمة; أ. د رعد ناصر مايود (Journal of College of Education, 2023)
The imagined place took a significant part of the Andalusian war poem. The Andalusian poet resorts to what saves him from the psychological, social and political pressures, and there is often in the imagination what fails from the nation. Weaving imagination, and every poet has his ability to imagine, and this ability differs from one poet to another. The poets of Andalusia in the poems of war, we find in them a clear statement in drawing a picture of war and the ability to imagine. Some of them draw a simple picture in their imagination close to reality, and some of them go to works of imagination